A method for preparing a composite layered oxide positive electrode material
By using a composite layered oxide preparation method in the positive electrode material of sodium ion battery, the stability and fluidity of the positive electrode material are improved by using the cladding materials of Al, Ti and Zr elements, and the problems of easy plate junction, high alkalinity and thermodynamic instability of the positive electrode material in the prior art are solved, and better battery performance is achieved.
Patent Information
- Application Number
- CN202310490088.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-05-04
AI Technical Summary
The existing sodium ion battery layered oxide positive electrode materials have problems such as easy plate bonding, high alkalinity and thermodynamic instability, resulting in poor material fluidity, difficulty in cell manufacturing process and easy decomposition of metal dissolution during electrochemical processes.
By using a composite layered oxide positive electrode material preparation method, the obtained positive electrode material has improved stability and fluidity by mixing the matrix material with the cladding material (including Al, Ti and Zr elements) evenly, and calcining, crushing, and sieving at high temperature to a specific particle size distribution.
Through the protection interface of the cladding material and the formation of the high-ion layer conductive cladding layer, the stability and flowability of the cathode material are significantly improved, and the capacity, rate performance and cycle life of the battery are improved.
Smart Images

Figure CN116514181B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a composite layered oxide positive electrode material. Background Art
[0002] The energy density of sodium-ion batteries is relatively low. Although layered oxide cathode materials have a high theoretical capacity, since metallic sodium is a relatively active alkali metal, sodium carbonates, oxides and hydroxides all exhibit strong alkalinity, easy water absorption and easy deterioration. Layered oxide cathode materials for sodium-ion batteries are no exception. Specifically, they are easy to compact, highly alkaline and thermodynamically unstable, resulting in poor material fluidity, difficult battery cell manufacturing, and easy decomposition of metal dissolution catalytic electrolytes during the electrochemical process.
[0003] Existing methods for modifying fluidity mainly target material morphology, particle size, moisture content, and stacking conditions, but improvements in material morphology and particle size are limited by the preparation process and have high requirements for equipment. In addition, the moisture content and stacking conditions have high requirements for environmental control and are difficult to change in the process.
[0004] At present, high alkalinity and thermodynamic instability are basically improved by three methods: water washing, doping with other elements and coating compounds. However, the water washing process is difficult to control and the process is complicated. The doping process with other elements is difficult to operate and it is difficult to achieve satisfactory results. In addition, the coating compounds are divided into active coating and inactive coating. In the sodium ion battery system, the sintering conditions of the active coating agent and the layered oxide positive electrode material are incompatible; although the inactive coating can effectively improve the cycle performance, the increase in the coating amount will affect the electrochemical performance of the positive electrode material, which is mainly manifested in the reduction of capacity and the decrease of rate performance. The existing preparation methods of positive electrode materials are complicated, and the sodium ion battery has problems such as low capacity and poor electrochemical performance. Summary of the invention
[0005] In view of the above analysis, an embodiment of the present invention aims to provide a method for preparing a composite layered oxide positive electrode material, so as to solve the problems that the positive electrode material prepared by the existing method has poor electrical properties, resulting in reduced capacity of sodium ion batteries, decreased rate performance, poor material consistency, and the like.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a composite layered oxide positive electrode material comprises the following steps:
[0008] (1) mixing a base material and a coating material uniformly to obtain a powder, wherein the coating material comprises three elements: Al, Ti and Zr;
[0009] (2) The powder is calcined at high temperature, crushed, and sieved to a particle size of 4 μm≤D10≤6 μm, 9 μm≤D50≤20 μm, 16 μm≤D90≤30 μm, and 0.5≤D50 / (D90-D10)≤1 to obtain the composite layered oxide positive electrode material.
[0010] Furthermore, in step (1), the general formula of the matrix material is Na x1 Cu y1 Mn z1 Li s1 Ni t1 Fe u1 O 2+nδ , among which, 0.9<x1≤0.95, 0.05≤y1≤0.20, 0.33≤z1≤0.40, 0.01≤s1≤0.07, 0.08≤t1≤0.22, 0.33≤u1≤0.40, 0<n≤0.05, -1≤δ≤3, x1+2y1+3z1+3u1+s1+2t1<4<x1+2y1+4z1+3u1+s1+3t1, y1+z1+s1+t1+u1=1.
[0011] Furthermore, in step (1), the general formula of the coating material is Na a1 Al b1 Ti c1 Zr d1 O2, among which, 0.3≤a1≤0.5, 0.3≤b1≤0.6, 0.1≤c1≤0.2, 0.2≤d1≤0.5, a1+3b1+4c1+4d1=4, b1+c1+d1=1.
[0012] Furthermore, in step (1), the molar ratio of the coating material to the base material is α, wherein 0<α≤0.1.
[0013] Furthermore, in step (2), the high temperature calcination temperature is 700 to 1200° C., and the calcination time is 8 to 36 hours.
[0014] Furthermore, in step (2), the heating rate during the high-temperature calcination process is 1 to 10°C / min.
[0015] Furthermore, the positive electrode material is an O3 type layered oxide.
[0016] Furthermore, the positive electrode material has an average peak height ratio of 0.01≤HI≤5.5 and an average peak area ratio of 0.05≤AI≤4.5 at (003) / (104).
[0017] Furthermore, the pH value of the positive electrode material is 11.40-12.05.
[0018] Furthermore, the repose angle ψ of the positive electrode material is ≤40°.
[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0020] (1) The coating material selected in the method of the present invention includes three elements: Al, Ti and Zr. The coating material can protect the interface on the surface of the positive electrode material, inhibit the decomposition of the electrolyte, and have a certain high-temperature flame retardant effect. It can also consume the residual alkali on the surface, further improving the stability of the positive electrode material.
[0021] (2) The method of the present invention controls the particle size distribution of the positive electrode material particles so that the average peak height ratio of the material at (003) / (104) satisfies 0.01≤HI≤5.5, and the average peak area ratio satisfies 0.05≤AI≤4.5. Therefore, the method of the present invention controls the morphology from both microscopic and macroscopic scales to achieve better material consistency;
[0022] (3) The method of the present invention forms a high ion layer conductive coating composed of inactive metal oxides and residual alkali on the surface of the material based on the morphology of the positive electrode material, so that the material is easy to be hardened, the alkalinity is high and the thermodynamic instability is improved. The positive electrode material of the present invention is a multi-element coating layer;
[0023] (4) In the method of the present invention, the metal elements of the positive electrode material are used in a specific ratio. Even if the molar ratio of the coating material is 0.1, the battery made of the positive electrode material prepared by the present invention can still maintain the capacity and rate performance without decreasing. More coating materials can reduce the contact between the material and the electrolyte and reduce side reactions, thereby improving the cycle life of the battery.
[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0026] Figure 1 This is a SEM image of the positive electrode material prepared in Comparative Example 1;
[0027] Figure 2 This is a SEM image of the positive electrode material prepared in Comparative Example 2;
[0028] Figure 3 This is a SEM image of the positive electrode material prepared in Comparative Example 3;
[0029] Figure 4 This is a SEM image of the positive electrode material prepared in Example 1;
[0030] Figure 5 This is a SEM image of the positive electrode material prepared in Example 2;
[0031] Figure 6 XRD diagrams of the positive electrode materials prepared in Example 1, Example 2, and Comparative Examples 1-3;
[0032] Figure 7 Schematic diagram of the shape of the positive electrode material prepared in the present invention.
[0033] Among them, 1- coating material, 2- base material. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0035] A specific embodiment of the present invention discloses a method for preparing a composite layered oxide positive electrode material, comprising the following steps:
[0036] (1) mixing a base material and a coating material uniformly to obtain a powder, wherein the coating material comprises three elements: Al, Ti and Zr;
[0037] (2) The powder is calcined at high temperature, crushed, and sieved to a particle size of 4 μm≤D10≤6 μm, 9 μm≤D50≤20 μm, 16 μm≤D90≤30 μm, and 0.5≤D50 / (D90-D10)≤1 to obtain the composite layered oxide positive electrode material.
[0038] Compared with the prior art, the coating material in the method of the present invention contains three elements, namely Al, Ti and Zr. The coating material can protect the interface on the surface of the positive electrode material, inhibit the decomposition of the electrolyte, and has a certain high-temperature flame retardant effect. It can also consume the residual alkali on the surface, thereby further improving the stability of the positive electrode material.
[0039] It should be noted that the three elements Al, Ti and Zr are added in the form of at least one of hydroxide, carbonate or hydroxide to prepare the positive electrode material of the present invention.
[0040] Specifically, in step (1), the general formula of the matrix material is Na x1 Cu y1 Mn z1 Lis1 Ni t1 Fe u1 O 2+nδ , among which, 0.9<x1≤0.95, 0.05≤y1≤0.20, 0.33≤z1≤0.40, 0.01≤s1≤0.07, 0.08≤t1≤0.22, 0.33≤u1≤0.40, 0<n≤0.05, -1≤δ≤3, x1+2y1+3z1+3u1+s1+2t1<4<x1+2y1+4z1+3u1+s1+3t1, y1+z1+s1+t1+u1=1.
[0041] Specifically, in step (1), the general formula of the coating material is Na a1 Al b1 Ti c1 Zr d1 O2, among which, 0.3≤a1≤0.5, 0.3≤b1≤0.6, 0.1≤c1≤0.2, 0.2≤d1≤0.5, a1+3b1+4c1+4d1=4, b1+c1+d1=1.
[0042] In the present invention, the prepared composite layered oxide positive electrode material comprises a base material and a coating material, wherein the coating material comprises three elements: Al, Ti and Zr.
[0043] Specifically, the general formula of the prepared composite layered oxide positive electrode material can be:
[0044] Na x1 Cu y1 Mn z1 Li s1 Ni t1 Fe u1 O 2+nδ / α(Na a1 Al b1 Ti c1 Zr d1 O2)
[0045] Among them, 0.9<x1≤0.95, 0.05≤y1≤0.20, 0.33≤z1≤0.40, 0.01≤s1≤0.07, 0.08≤t1≤0.22, 0.33≤u1≤0.40, 0<n≤0.05, -1≤δ≤3, 0<α≤0.1, 0.3≤a1≤0.5, 0.3≤b1≤0.6, 0.1≤c1≤0.2, 0.2≤d1≤0.5, a1+3b1+4c1+4d1=4, b1+c1+d1=1, x1+2y1+3z1+3u1+s1+2t1<4<x1+2y1+4z1+3u1+s1+3t1, y1+z1+s1+t1+u1=1.
[0046] In step (1), when preparing the positive electrode material of the above general formula, according to Na x1 Cu y1 Mn z1 Li s1 Ni t1 Fe u1 O 2+nδ / α(Na a1 Al b1 Ti c1 Zr d1 O2), weigh Na2CO3, Li2CO3, CuO, Fe2O3, Ni(OH)2, Al2O3, TiO2, ZrO2 and MnO2 as raw materials, mix them evenly to obtain powder.
[0047] It should be noted that the above inequality is to ensure that charge conservation can be achieved even when the valence is changed.
[0048] Specifically, in step (1), the molar ratio of the coating material to the base material is α, wherein 0<α≤0.1.
[0049] Specifically, in step (2), the high temperature calcination temperature is 700-1200°C, such as 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, and the calcination time is 8-36h, such as 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h.
[0050] In a preferred embodiment, the high temperature calcination temperature is 800 to 1100° C. and the calcination time is 12 to 20 hours.
[0051] Specifically, in step (2), the heating rate during high temperature calcination is 1 to 10° C. / min.
[0052] Exemplarily, the heating rate is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min.
[0053] In a preferred embodiment, the heating rate during high temperature calcination is 2 to 5° C. / min.
[0054] It should be noted that the present invention adopts the above-mentioned required calcination temperature for solid-phase reaction. If the temperature is too high, other structures will be formed. If the temperature is too low, the required solid-phase reaction will not occur. The calcination time is the required reaction time. If the time is too long, other structures will be formed. If the time is too short, the solid-phase reaction will not be thorough. The heating rate adopts the specific heating rate of the present invention. If the heating rate is too fast, the reaction will not have time to occur and enter the next step of reaction or require a higher temperature to continue the reaction. If the heating rate is too slow, the subsequent reaction will not occur, which greatly prolongs the heat treatment time and increases energy consumption.
[0055] Specifically, the calcination atmosphere is selected from air atmosphere or oxygen atmosphere.
[0056] Specifically, the positive electrode material is an O3 type layered oxide.
[0057] Specifically, the positive electrode material has an average peak height ratio of 0.01≤HI≤5.5 and an average peak area ratio of 0.05≤AI≤4.5 at (003) / (104).
[0058] The preferred solution is: 0.5≤HI≤4, 0.5≤AI≤3.
[0059] It should be noted that the larger the HI is, the larger the effective area of the (003) surface of the material is scanned, that is, the area perpendicular to the (003) surface is wide, which further indicates that the material has more lamellar structures rather than spherical structures; the smaller the HI is, the less complete the crystallization temperature or crystallization reaction of the positive electrode material is, which is manifested as a low crystallinity. The size of AI also has a similar rule to HI. AI also characterizes how wide the half-peak width of the characteristic peak is. The wider the half-peak width is, the more impurities there are or the lower the crystallinity is. The present invention controls the morphology from both microscopic and macroscopic scales to make the material more consistent.
[0060] It should be noted that the present invention conducts multiple XRD tests on the prepared positive electrode material, and obtains the above peak position report through peak searching and analysis processing using Jade 6.0 software.
[0061] Based on the above analysis, the present invention controls the raw materials and proportions of the positive electrode material to obtain a positive electrode material with better morphology and better consistency.
[0062] Specifically, the pH value of the positive electrode material is 11.40-12.05.
[0063] Specifically, the repose angle ψ of the positive electrode material is ≤40°.
[0064] In a preferred embodiment, the repose angle ψ of the positive electrode material is ≤30°.
[0065] It should be noted that the repose angle test in the present invention refers to GB / T11986-1989. The repose angle shows that the positive electrode material of the present invention has good fluidity.
[0066] It should be noted that the shape and structure diagram of the positive electrode material of the present invention is as follows Figure 7 As shown, the positive electrode material structure is composed of a base material layer with an irregular outer surface and a coating material layer coated on the outer surface of the base material layer. It is a core-shell structure in which the coating material 1 is coated on the surface of the base material 2. Based on the different ionic radius and oxygen binding ability of each metal element in the present invention, the surface shape of the base material 2 is irregularly connected to the coating material 1. The present invention, through the comprehensive effect of each metal element and the preparation method, prevents Al, Ti and Zr from diffusing into the inside of the base material 2. The microscopic particles of the positive electrode material of the present invention are arranged in layers. The coating material 1 can protect the interface, inhibit the decomposition of the electrolyte and have a certain high-temperature flame retardant effect on the surface of the positive electrode material, and can realize the consumption of the residual alkali on the surface, further improving the stability of the positive electrode material. The base material and the coating material of the positive electrode material of the present invention form an irregular interface, and have a certain particle size distribution (including D10, D50, D90) and a regular outer surface, good consistency, and very good fluidity.
[0067] The preparation method of the positive electrode material of the present invention is explained below with reference to specific examples.
[0068] Example 1
[0069] A method for preparing a composite layered oxide positive electrode material of this embodiment comprises the following steps:
[0070] (1) The general formula of the matrix material is Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2, the coating material is generally Na 0.49 Al 0.49 Ti 0.17 Zr 0.34 O2, the molar ratio of the coating material to the base material is α=0.1, and according to the stoichiometric ratio, Na2CO3, Li2CO3, CuO, Fe2O3, Ni(OH)2, Al2O3, TiO2, ZrO2 and MnO2 are weighed as raw materials, mixed evenly, and powder is obtained;
[0071] (2) The powder is calcined at 930°C in a compressed air atmosphere for 12 hours at a heating rate of 3°C / min to obtain a positive electrode material precursor, which is crushed and sieved to a particle size of 4μm≤D10≤6μm, 9μm≤D50≤20μm, 16μm≤D90≤30μm, 0.5≤D50 / (D90-D10)≤1 to obtain the composite layered oxide positive electrode material, denoted as B1. The positive electrode material is an O3 type material.
[0072] A composite layered oxide positive electrode material of this embodiment is an O3 type material, and the general formula is as follows: Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2 / 0.1(Na 0.49 Al 0.49 Ti 0.17 Zr 0.34 O2).
[0073] Example 1-1
[0074] The preparation method of a composite layered oxide positive electrode material in this embodiment is the same as that in embodiment 1, except that the general formula of the matrix material is Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2, the general formula of the coating material is Na 0.49 Al 0.49 Ti 0.17 Zr 0.34 O2, the molar ratio of the coating material to the base material is α=0.01, and the positive electrode material obtained in this example is recorded as B-1.
[0075] The composite layered oxide positive electrode material of this embodiment is an O3 type material, and the general formula is as follows: Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2 / 0.01(Na 0.49 Al 0.49 Ti 0.17 Zr 0.34 O2).
[0076] Example 2
[0077] A method for preparing a composite layered oxide positive electrode material of this embodiment comprises the following steps:
[0078] (1) The general formula of the matrix material is Na 0.93 Li 0.04 Cu 0.14 Mn 0.37 Ni 0.08 Fe 0.37 O2, the coating material is generally Na 0.49 Al 0.49 Ti 0.17 Zr 0.34 O2, the molar ratio of the coating material to the base material is α=0.01, and according to the stoichiometric ratio, Na2CO3, Li2CO3, CuO, Fe2O3, Ni(OH)2, Al2O3, TiO2, ZrO2 and MnO2 are weighed as raw materials, mixed evenly, and powder is obtained;
[0079] (2) The powder is calcined at 920°C in a compressed air atmosphere for 15 h at a heating rate of 3°C / min to obtain a positive electrode material precursor, which is crushed and sieved to a particle size of 4μm≤D10≤6μm, 9μm≤D50≤20μm, 16μm≤D90≤30μm, 0.5≤D50 / (D90-D10)≤1 to obtain the composite layered oxide positive electrode material, denoted as B3. The positive electrode material is an O3 type material.
[0080] A composite layered oxide positive electrode material of this embodiment is an O3 type material, and the general formula is as follows: Na 0.93 Li 0.04 Cu 0.14 Mn 0.37 Ni 0.08 Fe 0.37 O2 / 0.01(Na 0.49 Al 0.49 Ti 0.17 Zr 0.34 O2).
[0081] Example 3
[0082] A method for preparing a composite layered oxide positive electrode material of this embodiment comprises the following steps:
[0083] (1) The general formula of the matrix material is Na 0.93 Li 0.04 Cu 0.16 Mn 0.37 Ni 0.08 Fe 0.37 O2, the coating material is generally Na 0.3 Al 0.3 Ti 0.2 Zr 0.5O2, the molar ratio of the coating material to the base material is α=0.01, and according to the stoichiometric ratio, Na2CO3, Li2CO3, CuO, Fe2O3, Ni(OH)2, Al2O3, TiO2, ZrO2 and MnO2 are weighed as raw materials, mixed evenly, and powder is obtained;
[0084] (2) The powder is calcined at 920°C in a compressed air atmosphere for 15 h at a heating rate of 3°C / min to obtain a positive electrode material precursor, which is crushed and sieved to a particle size of 4μm≤D10≤6μm, 9μm≤D50≤20μm, 16μm≤D90≤30μm, 0.5≤D50 / (D90-D10)≤1 to obtain the composite layered oxide positive electrode material, denoted as B5. The positive electrode material is an O3 type material.
[0085] A composite layered oxide positive electrode material of this embodiment is an O3 type material, and the general formula is as follows: Na 0.93 Li 0.04 Cu 0.16 Mn 0.37 Ni 0.08 Fe 0.37 O2 / 0.01(Na 0.3 Al 0.3 Ti 0.2 Zr 0.5 O2).
[0086] Example 4
[0087] A method for preparing a composite layered oxide positive electrode material of this embodiment comprises the following steps:
[0088] (1) The general formula of the matrix material is Na 0.95 Cu 0.18 Mn 0.33 Ni 0.08 Fe 0.40 Li 0.01 O2, the coating material is generally Na 0.3 Al 0.3 Ti 0.2 Zr 0.5 O2, the molar ratio of the coating material to the base material is α=0.01, and according to the stoichiometric ratio, Na2CO3, Li2CO3, CuO, Fe2O3, Ni(OH)2, Al2O3, TiO2, ZrO2 and MnO2 are weighed as raw materials, mixed evenly, and powder is obtained;
[0089] (2) The powder is calcined at 920°C in a compressed air atmosphere for 15 h at a heating rate of 3°C / min to obtain a positive electrode material precursor, which is crushed and sieved to a particle size of 4μm≤D10≤6μm, 9μm≤D50≤20μm, 16μm≤D90≤30μm, 0.5≤D50 / (D90-D10)≤1 to obtain the composite layered oxide positive electrode material, denoted as B7. The positive electrode material is an O3 type material.
[0090] A composite layered oxide positive electrode material of this embodiment is an O3 type material, and the general formula is as follows: Na 0.93 Li 0.04 Cu 0.16 Mn 0.37 Ni 0.08 Fe 0.37 O2 / 0.01(Na 0.3 Al 0.3 Ti 0.2 Zr 0.5 O2).
[0091] Example 5
[0092] A method for preparing a composite layered oxide positive electrode material of this embodiment comprises the following steps:
[0093] (1) The general formula of the matrix material is Na 0.92 Cu 0.2 Mn 0.38 Ni 0.08 Fe 0.33 Li 0.01 O2, the coating material is generally Na 0.3 Al 0.3 Ti 0.2 Zr 0.5 O2, the molar ratio of the coating material to the base material is α=0.01, and according to the stoichiometric ratio, Na2CO3, Li2CO3, CuO, Fe2O3, Ni(OH)2, Al2O3, TiO2, ZrO2 and MnO2 are weighed as raw materials, mixed evenly, and powder is obtained;
[0094] (2) The powder is calcined at 920°C in a compressed air atmosphere for 15 h at a heating rate of 3°C / min to obtain a positive electrode material precursor, which is crushed and sieved to a particle size of 4μm≤D10≤6μm, 9μm≤D50≤20μm, 16μm≤D90≤30μm, 0.5≤D50 / (D90-D10)≤1 to obtain the composite layered oxide positive electrode material, denoted as B8. The positive electrode material is an O3 type material.
[0095] A composite layered oxide positive electrode material of this embodiment is an O3 type material, and the general formula is as follows: Na 0.92 Cu 0.2 Mn 0.38 Ni 0.08 Fe 0.33 Li 0.01 O2 / 0.01(Na 0.3 Al 0.3 Ti 0.2 Zr 0.5 O2).
[0096] Comparative Example 1
[0097] The preparation method of the positive electrode material of this comparative example is the same as that of Example 1, except that the Al in the coating material is replaced by Co, the Al2O3 in the raw material is replaced by Co3O4, and the coating material has the general formula of Na 0.49 Co 0.49 Ti 0.17 Zr 0.34 O2, the positive electrode material obtained in this comparative example is recorded as A1.
[0098] The general formula of the positive electrode material of this comparative example is:
[0099] Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2 / 0.1(Na 0.49 Co 0.49 Ti 0.17 Zr 0.34 O2).
[0100] Comparative Example 2
[0101] The preparation method of the positive electrode material of this comparative example is the same as that of Example 1, except that the general formula of the base material is Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2, the coating material is generally Na 0.50 Mg 0.25 Ti 0.35 Zr 0.40 O2, the molar ratio of the coating material to the base material is α=0.1, and the positive electrode material obtained in this comparative example is recorded as A3.
[0102] The positive electrode material of this comparative example has the following general formula:
[0103] Na 0.93 Li0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2 / 0.1(Na 0.50 Mg 0.25 Ti 0.35 Zr 0.40 O2).
[0104] Comparative Example 3
[0105] The preparation method of the positive electrode material of this comparative example is the same as that of Example 1, except that no coating material is added. The positive electrode material obtained in this comparative example is recorded as A5.
[0106] The general formula of the positive electrode material of this comparative example is Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2.
[0107] Comparative Example 4
[0108] The preparation method and general formula of the positive electrode material of this comparative example are the same as those of Example 1, except that the particle size is screened to 1 μm≤D10<4 μm, 5 μm≤D50<9 μm, 10 μm≤D90<16 μm, 0.5≤D50 / (D90-D10)≤1. The positive electrode material prepared in this comparative example is recorded as C1.
[0109] Comparative Example 5
[0110] The preparation method and general formula of the positive electrode material of this comparative example are the same as those of Example 1, except that the particle size is screened to 6μm<D10<8μm, 20μm<D50<24μm, 25μm≤D90<30μm, 0.5≤D50 / (D90-D10)≤1. The positive electrode material prepared in this comparative example is recorded as C2.
[0111] Comparative Example 6
[0112] The preparation method of the positive electrode material of this comparative example is the same as that of Example 1, except that the general formula of the base material is Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2, the general formula of the coating material is Na 0.49 Al 0.49 Ti 0.17 Zr 0.34O2, the molar ratio of the coating material to the base material is α=0.11, and the positive electrode material prepared in this comparative example is recorded as C3.
[0113] The general formula of the positive electrode material prepared in this comparative example is:
[0114] Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2 / 0.11(Na 0.49 Al 0.49 Ti 0.17 Zr 0.34 O2).
[0115] Comparative Example 7
[0116] The preparation method of the positive electrode material of this comparative example is the same as that of Example 1, except that the general formula of the base material is Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2, the general formula of the coating material is Na 0.2 Al 0.2 Ti 0.27 Zr 0.53 O2, the molar ratio of the coating material to the base material is α=0.01, and the positive electrode material prepared in this comparative example is recorded as C4.
[0117] The general formula of the positive electrode material prepared in this comparative example is:
[0118] Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2 / 0.01(Na 0.2 Al 0.2 Ti 0.27 Zr 0.53 O2).
[0119] Comparative Example 8
[0120] The preparation method of the positive electrode material of this comparative example is the same as that of Example 1, except that the general formula of the base material is Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2, the general formula of the coating material is Na 0.6Al 0.6 Ti 0.13 Zr 0.27 O2, the molar ratio of the coating material to the base material is α=0.01, and the positive electrode material prepared in this comparative example is recorded as C5.
[0121] The general formula of the positive electrode material prepared in this comparative example is:
[0122] Na 0.93 Li 0.04 Cu 0.07 Mn 0.37 Ni 0.15 Fe 0.37 O2 / 0.01(Na 0.6 Al 0.6 Ti 0.13 Zr 0.27 O2).
[0123] Comparative Example 9-1
[0124] The preparation method and general formula of the positive electrode material prepared in this comparative example are the same as those in Example 2, except that the temperature of high-temperature calcination in the preparation method is 1250° C. The positive electrode material prepared in this comparative example is recorded as C9-1.
[0125] Comparative Example 9-2
[0126] The preparation method and general formula of the positive electrode material prepared in this comparative example are the same as those in Example 2, except that the temperature of high-temperature calcination in the preparation method is 690° C. The positive electrode material prepared in this comparative example is recorded as C9-2.
[0127] Comparative Example 9-3
[0128] The preparation method and general formula of the positive electrode material prepared in this comparative example are the same as those in Example 2, except that the high-temperature calcination time in the preparation method is 37 hours. The positive electrode material prepared in this comparative example is recorded as C9-3.
[0129] Comparative Example 9-4
[0130] The preparation method and general formula of the positive electrode material prepared in this comparative example are the same as those in Example 2, except that the high-temperature calcination time in the preparation method is 7 hours. The positive electrode material prepared in this comparative example is recorded as C9-4.
[0131] Comparative Example 9-5
[0132] The preparation method and general formula of the positive electrode material prepared in this comparative example are the same as those in Example 2, except that the heating rate in the high-temperature calcination in the preparation method is 11°C / min. The positive electrode material prepared in this comparative example is recorded as C9-5.
[0133] Comparative Example 9-6
[0134] The preparation method and general formula of the positive electrode material prepared in this comparative example are the same as those in Example 2, except that the heating rate in the high-temperature calcination in the preparation method is 0.5°C / min. The positive electrode material prepared in this comparative example is recorded as C9-6.
[0135] Test Example 1
[0136] (1) The positive electrode materials prepared in Examples 1-5 and Comparative Examples 1 to 9-6 were respectively used as active materials, mixed according to the mass ratio of active material: SP: PVDF of 90:5:5, NMP was added to make a viscous glue, coated on aluminum foil, and baked in a vacuum drying oven at 120°C for 12h to obtain a positive electrode sheet. A metal sodium sheet was used as a counter electrode, glass fiber (Waterman) was used as a diaphragm, 1mol / LNaPF6EC / DMC=1:1 (Alfa) was used as an electrolyte, and a 2032 button cell was assembled in an Ar protective glove box. The battery was tested in the voltage range of 2.5 to 4.0V, activated at 0.1C for three weeks, cycled at 0.5C for 3 weeks, and cycled at 1C for 3 weeks. The 0.1C first week discharge specific capacity and coulomb efficiency, 0.5C first discharge specific capacity and 1C first discharge specific capacity were recorded, and the results are shown in Table 1.
[0137] Among them, the physical properties are characterized as follows:
[0138] pH test: Take the positive electrode material and distilled water in a mass ratio of 1:20, stir magnetically for 10 minutes, let it stand for 5 minutes, and measure the pH value, which is recorded as the material pH;
[0139] XRD test: range 10-80 degrees, step length 0.02 degrees, time 0.2, total time 712 seconds;
[0140] SEM test: acceleration voltage 10kV, resolution 10k, general morphology shooting;
[0141] Repose angle test: see GB / T11986-1989.
[0142] The relevant data of pH, repose angle ψ and XDR are shown in Table 2.
[0143] Table 1
[0144]
[0145] As can be seen from Table 1, compared with B1, A1 replaces Co with Al in the coating material. Although the performance of Co and Al is relatively close, the 0.1C first-week discharge capacity of the battery decreases by 4.22mAh / g after Co replaces Al. Compared with B1, when the coating material of A3 is replaced by Mg-Ti-Zr from Al-Ti-Zr, the 0.1C first-week discharge capacity of the battery decreases by 3mAh / g. The above shows that the base material and the coating material must be used in a specific combination to play a role in improving the battery capacity.
[0146] Compared with B1-1, when α is at a smaller value of 0.01 and a larger value of 0.1, the specific capacity and coulombic efficiency of the battery are similar, and there is no significant decrease in capacity and rate performance at a larger value of 0.1. This shows that the positive electrode material of the present invention adopts a specific ratio of each metal element, and even if the molar ratio of the coating material accounts for 0.1, the positive electrode material prepared by the present invention can still maintain the capacity and rate performance without decreasing. More coating materials can reduce the contact between the material and the electrolyte and reduce side reactions, thereby improving the cycle life.
[0147] Compared with B1, the battery capacity and coulombic efficiency of C1-C2 are lower, because only the positive electrode material particle size of the present invention has a higher battery capacity and coulombic efficiency.
[0148] Compared with B1, the battery capacity and coulombic efficiency of C3-C5 are reduced. This is because only the positive electrode material prepared with the ratio of each element of the present invention has a higher battery capacity and coulombic efficiency.
[0149] Compared with C9-1 to C9-6, the temperature, time and heating rate of high-temperature calcination of B3 need to be controlled within the range specified by the present invention. Too high or too low will have a greater impact on the battery capacity and coulombic efficiency.
[0150] Table 2
[0151] Material pH Angle of repose ψ AI HI B1 11.56 28° 0.812 0.867 B1-1 11.58 29° 0.817 0.885 B3 11.74 29° 0.760 0.820 B5 11.48 28° 0.934 0.848 B7 11.57 30° 0.956 0.837 B8 11.56 30° 0.949 0.849 A1 12.25 42° 0.419 0.394 A3 12.32 41° 0.421 0.369 A5 12.61 44° 4.132 5.263 C1 12.21 41° 0.845 0.643 C2 11.57 36° 0.962 1.541 C3 11.52 29° 0.786 0.798 C4 11.73 30° 0.751 0.812 C5 11.92 33° 0.781 0.853 C9-1 11.28 32° 4.532 5.535 C9-2 12.98 45° 0.049 0.009 C9-3 11.37 35° 4.501 5.514 C9-4 12.85 41° 0.379 0.642 C9-5 12.75 44° 3.782 4.526 C9-6 11.41 38° 0.231 0.563
[0152] It can be seen from Table 2 that A5 does not use coating materials, and its repose angle ψ is greater than 40°. Compared with A5, A1 and A3 use Co-Ti-Ni and Mg-Ti-Zr as coating materials, and their repose angles and pH values have decreased to a certain extent. However, compared with B1 with a repose angle of less than 30° and pH of less than 12, the effect is not obvious enough.
[0153] Since, in terms of technology, an angle of repose of less than 30° is defined as very good fluidity, 31-35° is good fluidity, an angle of repose of more than 40° is qualified fluidity, an angle of repose of more than 45° is poor fluidity, an angle of repose of more than 55° is very poor fluidity, and an angle of repose of more than 66° is difficult to flow, it can be seen from the angles of repose of materials B1 to B8 of the present invention that the materials after coating have good fluidity.
[0154] Compared with B1, C1-C2 has a larger repose angle, which is because the positive electrode material prepared by using the particle size of the present invention has better fluidity.
[0155] Compared with B1, C3-C5 indicates that the content of either α or sodium in the coating material exceeds the specified range of the present invention, which not only affects the electrochemical properties of the material, but also affects the angle of repose and pH.
[0156] Compared with B3, the temperature, time and heating rate of high-temperature calcination of C9-1 to C9-6 need to be controlled within the range specified by the present invention. Too high or too low a temperature will have a greater impact on the pH and repose angle of the material.
[0157] (2) The positive electrode materials prepared in Comparative Examples 1-3 and Examples 1 and 2 were subjected to SEM and XRD tests, as shown in Figures 1-6, respectively.
[0158] The SEM images of the analyzed materials are as follows:
[0159] The SEM images of B1 and B3 materials are shown in Figure 4 and 5 As shown, from Figure 4-5 It can be seen that although there are some fine particles attached to the surface of the material particles, the overall surface is relatively clean. Figure 4 This indicates that after the positive electrode material is coated with the coating material of the present invention, the contact with air during the preparation and testing process is reduced, and the surface side reaction basically does not occur.
[0160] The SEM images of A1, A3 and A5 materials are shown in Figure 1-3 As shown, the particle surface of the material is full of dot particles and other fine particles. Figure 3 The most obvious is the large flaky particles, which indicates that the positive electrode material prepared without the coating material specified in the present invention or without the coating material has serious side reactions in the air contact during the preparation and testing process, and the material tends to become viscous, the particles stick together, and the fluidity becomes poor.
[0161] from Figure 6 It can be seen from the figure that, compared with the characteristic peaks of the layered cathode material (* marked with asterisk (003), *' marked with asterisk (104)), after being coated with the coating material, HI and AI can also be within the specified range. This indicates that the sodium salt coating of the specific three oxides can make HI and AI within the specified range, and the particle morphology is spherical.
[0162] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a composite layered oxide positive electrode material, characterized in that: The steps include: (1) Na2CO3, Li2CO3, CuO, Fe2O3, Ni(OH)2, Al2O3, TiO2, ZrO2 and MnO2 are mixed as raw materials to obtain powder; (2) calcining the powder at high temperature, crushing, and sieving to a particle size of 4 μm ≤ D10 ≤ 6 μm, 9 μm ≤ D50 ≤ 20 μm, 16 μm ≤ D90 ≤ 30 μm, and 0.5 ≤ D50 / (D90-D10) ≤ 1 to obtain the composite layered oxide positive electrode material; Wherein, the composite layered oxide positive electrode material is a core-shell structure in which the coating material is coated on the surface of the base material; The general formula of the matrix material is Na x1 Cu y1 Mn z1 Li s1 Ni t1 Fe u1 O 2+nδ , where 0.9<x1≤0.95, 0.05≤y1≤0.20, 0.33≤z1≤0.40, 0.01≤s1≤0.07, 0.08≤t1≤0.22, 0.33≤u1≤0.40, 0<n≤0.05, -1≤δ≤3, x1+2y1+3z1+3u1+s1+2t1<4<x1+2y1+4z1+3u1+s1+3t1, y1+z1+s1+t1 +u1=1; The general formula of the coating material is Na a1 Al b1 Ti c1 Zr d1 O2, where 0.3≤a1≤0.5, 0.3≤b1≤0.6, 0.1≤c1≤0.2, 0.2≤d1≤0.5, a1+3b1+4c1+4d1=4, b1+c1+d1=1; The general formula of the composite layered oxide positive electrode material is: Na x1 Cu y1 Mn z1 Li s1 Ni t1 Fe u1 O 2+nδ / α(Na a1 Al b1 Ti c1 Zr d1 O2); The molar ratio of the coating material to the base material is α, where 0<α≤0.1; In step (2), the high temperature calcination temperature is 700-1200°C, and the calcination time is 8-36 hours.
2. The method for preparing the composite layered oxide positive electrode material according to claim 1, characterized in that: In step (2), the heating rate during the high-temperature calcination process is 1-10°C / min.
3. The method for preparing the composite layered oxide positive electrode material according to claim 1, characterized in that: The positive electrode material is O3 type layered oxide.
4. The method for preparing the composite layered oxide positive electrode material according to claim 1, characterized in that: The positive electrode material has an average peak height ratio of 0.01≤HI≤5.5 and an average peak area ratio of 0.05≤AI≤4.5 at (003) / (104).
5. The method for preparing the composite layered oxide positive electrode material according to claim 1, characterized in that: The pH value of the positive electrode material is 11.40-12.
05.
6. The method for preparing the composite layered oxide positive electrode material according to claim 1, characterized in that: The repose angle ψ of the positive electrode material is ≤40°.
Citation Information
Patent Citations
Layered oxide sodium ion battery positive electrode material
CN115117323A
Composite layered oxide positive electrode material and sodium ion battery
CN116190632A